Ekosistem Dan Peran Lembaga Keagamaan Yahudi Dalam Pembentukan Identitas Sosial Dan Spiritualitas Komunitas Yahudi - Fika; Tasya; Ahmad Jaiz (4, 2026)
This research examines the institutional dynamics of Judaism as the oldest Abrahamic religion that underwent a fundamental transformation after the destruction of the Second Temple in 70 CE. This historical event triggered a profound institutional crisis, due to the loss of the main center of worship based on the cult of sacrifice. This condition prompted a process of re-institutionalization pioneered by Rabbi Yohanan ben Zakkai in Yamnia (Yavneh), by shifting religious orientation from the Temple to the authority of sacred texts and intellectual traditions, especially the Torah, Talmud, and Halakha. This research uses a descriptive qualitative approach through a literature study of classical and modern sources, to analyze the main elements of Jewish institutions, including the synagogue as the center of worship and community life, rabbinic authority, religious educational institutions (yeshivas), and the development of modern denominations such as Orthodox, Reform, and Conservative. The results of the study indicate that the institutional resilience of Judaism is built through a synergy between the ritual, legal, and social dimensions that reinforce each other. Synagogues function not only as prayer spaces but also as educational, social, and community identity centers, while rabbinic authority gains legitimacy through its interpretive power over sacred texts. The intertextuality between the Tanakh, Talmud, and Midrash has been shown to strengthen this authority and maintain the cohesion of religious identity amidst Diaspora life. Furthermore, this study finds significant institutional divergence between the Israeli and American contexts, where Israel is dominated by the Orthodox Chief Rabbinate, while in the United States, Reform and Conservative denominations are more developed and adapt to modern values. Abstrak Penelitiannya ini mengkaji dinamika kelembagaan Yudaisme sebagai agama Abrahamik tertua yang mengalami transformasi fundamental pasca-penghancuran Bait Suci Kedua pada tahun 70 M. Peristiwa historis tersebut memicu krisis institusional yang mendalam, karena hilangnya pusat ibadah utama berbasis kultus kurban. Kondisi ini mendorong proses institusionalisasi ulang yang dipelopori oleh Rabi Yohanan ben Zakkai di Yamnia (Yavneh), dengan mengalihkan orientasi keagamaan dari Bait Suci menuju otoritas teks suci dan tradisi intelektual, khususnya Taurat, Talmud, dan Halakha. Penelitian ini menggunakan pendekatan kualitatif deskriptif melalui studi pustaka terhadap sumber-sumber klasik dan modern, guna menganalisis elemen-elemen utama kelembagaan Yahudi, meliputi sinagoga sebagai pusat ibadah dan kehidupan komunitas, otoritas rabinik, lembaga pendidikan keagamaan (yeshiva), serta perkembangan denominasi modern seperti Ortodoks, Reformasi, dan Konservatif. Hasil penelitian menunjukkan bahwa ketahanan institusional Yudaisme terbangun melalui sinergi antara dimensi ritual, hukum, dan sosial yang saling menguatkan. Sinagoga berfungsi tidak hanya sebagai ruang ibadah, tetapi juga sebagai pusat pendidikan, sosial, dan identitas komunitas, sementara otoritas rabinik memperoleh legitimasi melalui kemampuan interpretatif atas teks-teks suci. Intertekstualitas antara Tanakh, Talmud, dan Midrash terbukti memperkuat otoritas tersebut serta menjaga kohesi identitas keagamaan di tengah kehidupan Diaspora. Selain itu, penelitian ini menemukan adanya divergensi kelembagaan yang signifikan antara konteks Israel dan Amerika Serikat, di mana Israel didominasi oleh Rabbinate Kepala Ortodoks, sedangkan di Amerika Serikat lebih berkembang denominasi Reformasi dan Konservatif yang adaptif terhadap nilai-nilai modernitas.